Association Between Thymosin β4 and Coronary Arterial Lesions in Children with Kawasaki Disease - Wu J; Yang P; Zhang J; Chen Z; Wei Y; Su Y; Yi Q (Journal of Inflammation Research)
Jinhui Wu, Penghui Yang, Jing Zhang, Zhuo Chen, Yi Wei, Ya Su, Qijian Yi Department of Cardiovascular Medicine, Ministry of Education Key Laboratory of Child Development and Disorders, Chongqing Key Laboratory of Pediatric Metabolism and Inflammatory Diseases, Key Laboratory of Children’s Important Organ Development and Diseases of Chongqing Municipal Health Commission, National Clinical Research Center for Child Health and Disorders, National Clinical Key Cardiovascular Specialty, Children’s Hospital of Chongqing Medical University, Chongqing, 400014, People’s Republic of ChinaCorrespondence: Ya Su, Department of Cardiovascular Medicine, Children’s Hospital of Chongqing Medical University, Chongqing, 400014, People’s Republic of China, Tel/Fax +86 02363624344, Email suya@hospital.cqmu.edu.cn Qijian Yi, Department of Cardiovascular Medicine, Children’s Hospital of Chongqing Medical University, Chongqing, 400014, People’s Republic of China, Tel/Fax +86 02363624344, Email qjyi2003@hotmail.comBackground: Kawasaki disease (KD) is an acute systemic vasculitis primarily affecting children and is a leading cause of acquired heart disease in developed countries. Recently, an increasing number of studies have demonstrated the close correlations between inflammation and KD. Thymosin β 4 (Tβ 4) has been reported to play a role in cardiovascular protection and repair by modulating inflammation, angiogenesis, and endothelial function. However, its role in KD still remains poorly understood. This study aims to explore the potential involvement of Tβ 4 in the pathogenesis of KD, with a particular focus on its relationship to inflammation and coronary artery lesions (CALs).Methods: Serum Tβ 4 levels were measured using enzyme-linked immunosorbent assay (ELISA) in children with KD and age-matched healthy controls. The KD group was further categorized into patients with and without CALs. Correlation analyses were performed between Tβ 4 levels and clinical or laboratory parameters.Results: Serum Tβ 4 levels were significantly lower in patients with KD compared to healthy controls and were further reduced in patients with CALs. After intravenous immunoglobulin (IVIG) treatment, Tβ 4 levels significantly increased. Tβ 4 levels were negatively correlated with several pro-inflammatory (eg, TNF-α, IL-1β) and anti-inflammatory cytokines (eg, IL-4, IL-10).Conclusion: Tβ 4 levels were significantly lower in children with KD, particularly in those with CALs. These findings suggest that Tβ 4 may be involved in the inflammatory pathogenesis of KD and the progression of CALs, thus could represent a potential target for future diagnostic or therapeutic interventions.Keywords: cytokine, anti-inflammatory, intravenous immunoglobulin, angiogenesis